Status and Needs of Continuing Education for Trauma Nursing - Yooun-Joong Jung; Suhyun Kim; Sangmi Noh; Eunkyoung Seo; Soyoung Jung; Jiyoung Kim (Journal of Trauma and Injury)
Purpose This study was conducted to status and needs for continuing education for trauma hospital nurses in Korea. Methods Thirty nurses from the seven level I trauma center hospitals or trauma treatment systems were randomly selected and surveyed. The survey was conducted from March 1 to May 31, 2017. Categorical data were analyzed with Pearson chi-square tests and Continuous variables were analyzed with ANOVA. Results Only 86 out of 204 nurses had received continuing education (42.1%). The current status of continuing education programs, delivering institution (p<0.001), education method (p<0.001), education period (p=0.003), number of participants (p=0.007), and instructors (p=0.014) were also significantly different from trauma center to trauma center. There were 108 (52.9%) nurses who responded that continuing education programs were “needed” 92 (45.1%) and “very much needed 16 (7.8%). According to each trauma center’s characteristics were significantly differences in the need for continuing education (p=0.089), subject selection method (p<0.001) and the number of continuing education sessions (p=0.043) depending on the hospital. Conclusions It is necessary to consider differences between the hospitals to develop continuing education programs that reflect the needs of nurses, in order to improve the efficiency of and satisfaction with the educational programs.